LEXICAL RELATIONS IN KELLY CLARKSON’S SONGS - Muhammad . Guntar (LINGUISTIK TERAPAN, 2022)
This study is about analysis of lexical relations in Kelly Clarkson’s songs. The aim of this study is to find out types of lexical relations by Saeed’s theory that have been found in Kelly Clarkson’s songs and which most dominant lexical relations found in Kelly Clarkson’s songs. This study emerges from the qualitative research. The writer used several Kelly Clarkson’s songs namely Piece by Piece, Breakaway, Dark Side and Miss Independent as the data sources. The finding of this study is categorized by Saeed’s theory namely homonym, polysemy, synonymy, antonym, hyponymy, and meronymy. The results of the study found out synonymy, antonymy, polysemy, homonymy, hyponymy, and meronymy in Kelly Clarkson’s songs. The most dominant lexical relations found in those songs is polysemy. It was found 7 cases from 20 cases in total. Polysemy is a less well-known term than synonym or antonym, although it relates to a far more significant sense relationship. In one word, it can describe two or more meanings.